Influence of structural disorder on magnetic and transport properties of (La0.7Sr0.3)0.5(Pr0.65Ca0.35)0.5MnO3 films - Prokhorov, V.G.; Flis, V.S.; Kaminsky, G.G.; Lee, Y.P.; Park, J.S.; Svetchnikov, V.L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
Magnetic and transport properties of (La0.7Sr0.3)0.5(Pr0.65Ca0.35)0.5MnO3) films prepared by a «co-deposition» utilizing the laser-ablation technique are investigated in a wide temperature range. The film deposited at 300˚C has a nano-crystalline disordered structure and exhibits a paramagnetic temperature dependence of the magnetization with a narrow peak (DT ≃ 10 K) at TG ≃ 45 K, which can be interpreted as a paramagnetic → superparamagnetic transition. A short-term annealing of the as-deposited film at 750 ˚C leads to the formation of a high-textured polycrystalline microstructure and to the appearance of ferromagnetic (FM) and metal—insulator (MI) transitions at TC ≃ 240 K and TP ≃ 140 K, respectively. The observed discrepancy between TP and TC values can be ascribed to a percolating nature of the MI transition, with an exponent of 5.3 for the percolating conductivity. The film deposited at Tsub ≃ 740 ˚C is composed of the lattice strain-free and the lattice-strained crystallites with different lattice parameters and TC‘s, and is consistently described in the framework of the Millis model [A.J. Millis, T. Darling, and A. Migliori, J. Appl. Phys. 83, 1588 (1998)]. For a single-phase crystalline film obtain TC ≃ 270 K and TP ≃ 260 K.